If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 5m + -4 = 9m + 8 + -3 Reorder the terms: 9 + -4 + 5m = 9m + 8 + -3 Combine like terms: 9 + -4 = 5 5 + 5m = 9m + 8 + -3 Reorder the terms: 5 + 5m = 8 + -3 + 9m Combine like terms: 8 + -3 = 5 5 + 5m = 5 + 9m Add '-5' to each side of the equation. 5 + -5 + 5m = 5 + -5 + 9m Combine like terms: 5 + -5 = 0 0 + 5m = 5 + -5 + 9m 5m = 5 + -5 + 9m Combine like terms: 5 + -5 = 0 5m = 0 + 9m 5m = 9m Solving 5m = 9m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-9m' to each side of the equation. 5m + -9m = 9m + -9m Combine like terms: 5m + -9m = -4m -4m = 9m + -9m Combine like terms: 9m + -9m = 0 -4m = 0 Divide each side by '-4'. m = 0 Simplifying m = 0
| y/16=-26 | | 86-w=170 | | -1.56-1= | | 5cos(2x)= | | -3.3x=36.96 | | -4.1+7x=7.1 | | Y=2+3x(6-y) | | 10.24*-8= | | 2(-1/2x)(3-2x)=0 | | 8-6z=38 | | -21+35+(-37)+27= | | 5x-Y-100=0 | | -10.24*4= | | 2x+y-600=0 | | 8y+9=21 | | 13x-(7x-4)=28 | | x^8+5x^7+6x^6= | | -5.24-5= | | 4/7x=2 | | 3x+8y=3 | | x-2(x+2)+3(5x)=30 | | 128=4*7*4+2*4*h | | 2y^2+9y-6x-(1.875)=0 | | 2(4x-1)-(5x-4)=7-(3x+2) | | 2y^2+9y-6x-(2.25)=0 | | 104=4(20)+8(2h) | | G/3=-6 | | G/3=-3 | | 0.4x-0.1=0.5-0.6(9-2x) | | 9y-1=9y-y | | 5x+3x=7x-4 | | 6x^4-5x^3-4x^2=0 |